Management of patients with heart failure using education or education & yelephone or telephone in Cyprus (MEETTinCy) trial. Preliminary results - Lambrinou, Ekaterini; Kalogirou, Fotini; Protopapas, Andreas; Papathanassoglou, Elizabeth; Barberis, Vassilis I. I.; Sourtzi, Panayota A.; Lemonidou, Chryssoula; Middleton, Nicos (My University, 2013)
Background: Heart Failure (HF) is a chronic condition with an enormous socio-economic cost. Disease management strategies that promote the adoption of self-carepractices are promising in improving HF outcomes.Aim: The aim of the project MEETTinCy is to evaluate the effectiveness of a nurse-ledprogramme which includes predischarge education and/ or telephone education andsupport on improving HF patients’ quality of life (QoL) and self-care behaviours.Methods: Hospitalized patients with HF, NYHA I-IV, were recruited from four general hospitals of Cyprus to participate in a randomized controlled trial with 4 arms. Eligiblepatients were randomly assigned to receive pre-discharge education or telephonesupport for 3 months after discharge or both, while patients in the control groupreceived the usual care. Measures of self-care (using the European Heart Failure Self-care Behavior Scale) and QoL (using the Minnesota Living in Heart Failure Question-naire) were collected at baseline and 3 months. Initial results of the observed mean dif-ferences in QoL and self-case scores during the 3 month period are presented here.Results: To date, complete self-care measures were available for 123 participants andQoL measures for 83. Baseline evaluation revealed well-matched groups. In terms ofabsolute values, improvement in QoL scores favored the intervention groups thoughthe observed differences were not statistically significant. The greatest improvementin Qol was observed among participants in the telephone support group [13.34 95%CI (4.3, 22.3)], followed by the predischarge education plus telephone supportgroup [13.00 95% CI (5.37, 20.62]. However, no differences were observed withregards to self-care scores in-between the groups.Conclusion: Preliminary results of MEETTinCy suggest that the telephone supporteither alone or in combination with predischarge education, has the potential toimprove HF patients’ QoL, even though it did not necessarily improve self-care beha-viours. It is anticipated that results will reach statistical significance once the finalsample of 300 is recruited.